Book Review Hospitality Marketing: Principles and Practice (2nd ed.) (Malaysian Management Journal, 2010)
The ideal person to write a review of books is definitely someone who has written a textbook himself. Bowie and Buttle indeed have made a promising effort to disseminate an important perspective on a subject related to hospitality. One might be quick to conclude that this text is just a dime a dozen and a window dressing of the first edition since not much space is dedicated to reflect on marketing theory and practice to the level of the state of the art. But this sort of unfair review is best left to those scholars who had experienced writing a textbook which is celebrated throughout the English speaking world, like Kotler or Drucker. The review here is a modest attempt to guide those who seek some idea and facts about the book before purchasing it.